Commuting experience and its effects to selected working parents - San Agustin, Leslie Antoniette A. (College of Home Economics, University of the Philippines Diliman, 2016)
This is a descriptive study which investigated how selected working parents describe their commuting experience and the effects on their personal, professional, and family lives. This research used qualitative and quantitative measures and is exploratory in nature. A survey questionnaire was developed from the results of extensive interviews in a pilot study. The questionnaire included semantic differential scale to describe commuting experience and Likert type scale to measure the negative effects of commuting to personal, professional, and family life. Data was gathered from 46 commuting parents selected through purposive sampling and was analyzed using frequency distribution. Results showed that many of these parents travel across municipalities or cities and they usually take 2 to 3 rides in order to arrive at their workplace. On the average they spend around Php 60.00 for travel fare. Most respondents (62%) have a slightly to moderately negative commuting experience. Respondents reported negative effects of commuting to the different areas of their lives. Majority of the respondents experience negative effects in personal life, such as always hurrying up in the morning, tiredness, and stress. For the professional life, although most of them have decreased motivation and time adjustments, many still perceived a high job performance. Many respondents said they had less quality time for the family and in taking care of children. Thus, public commuting is mostly a negative experience for the respondents and has negative effects on personal, professional, and family life.